2016
DOI: 10.1007/s11250-016-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro acaricidal activity of Bobgunnia madagascariensis Desv. against Amblyomma variegatum (Fabricius) (Acari: Ixodidae)

Abstract: The objective of the study was to determine the acaricidal properties of Bobgunnia madagascariensis (Desv.) J.H. Kirkbr. and Wiersema (Leguminosae) against adult Amblyomma variegatum (Fabricius) ticks, using Tephrosia vogelii Hook.f. (Leguminosae) as a positive control. Plant extracts of both were prepared using methanol, acetone and chloroform as extraction solvents. Methanol leaf extracts of T. vogelii (0.014 g) and methanol fruit extracts of B. madagascariensis (0.0062 g) gave the highest mean extraction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Many species of plants have been evaluated for acaricidal activity, with the species studied mainly being members of the families Poaceae, Fabaceae, Lamiaceae, Verbenaceae, Piperaceae and Asteraceae (Borges et al 2011 ; Muyobela et al 2016 ; Dantas et al 2016 ). Some studies have identified secondary metabolites (terpenes, stilbenes, coumarins, alcohols, acids, sulfurated compounds and aldehydes) of essential oils and plant extracts, associated with acaricidal effects against the genera Amblyomma , Rhipicephalus , Hyalomma , Dermacentor , Argas and Ixodes (Pamo et al 2005 ; Cetin et al 2010 ).…”
Section: Non-acaricidal Control Of Ticksmentioning
confidence: 99%
“…Many species of plants have been evaluated for acaricidal activity, with the species studied mainly being members of the families Poaceae, Fabaceae, Lamiaceae, Verbenaceae, Piperaceae and Asteraceae (Borges et al 2011 ; Muyobela et al 2016 ; Dantas et al 2016 ). Some studies have identified secondary metabolites (terpenes, stilbenes, coumarins, alcohols, acids, sulfurated compounds and aldehydes) of essential oils and plant extracts, associated with acaricidal effects against the genera Amblyomma , Rhipicephalus , Hyalomma , Dermacentor , Argas and Ixodes (Pamo et al 2005 ; Cetin et al 2010 ).…”
Section: Non-acaricidal Control Of Ticksmentioning
confidence: 99%
“…For example, many plant species known in Africa for their insecticidal properties are also reported to be used for poisoning fish (Neuwinger 2004) including many species in the Leguminosae. The toxicity of these species is often associated with saponins and rotenoids and many of these species have bioactivity against pest insects or are used in pest management, including Tephrosia vogelii (Stevenson et al 2012 (Muyobela et al 2016, Sarasan et al 2011Stevenson et al 2009). Consequently great care must be taken in deploying plants for pest management that have potential toxicity to aquatic fauna; in some regions, their use may need to be restricted in proximity to waterways.…”
Section: Safety and Exposure To Toxic Plant Compoundsmentioning
confidence: 99%
“…Whereas, various alcoholic extracts (ethanolic and methanolic) of different parts for numerous plants, e.g. Acmella oleracea, Ageratum conyzoides, Aloe rupestris, Argemone mexicana, Artemisia absinthium, Berberis tinctoria, Caesalpinia gaumeri, Cissus quadrangularis, Clematis brachiata, Cleome gynandra, Dalbergia sissoo, Datura metel, D. stramonium, Dodonaea viscose, Eupatorium adenophorum, Euphorbia rothiana, Neoglaziovia variegata, Ficus sycomorus, Lobelia leschenaultiana, Monsonia angustifolia, Pelargonium luridium, Semecarpus anacardium, Solanum sisymbrifolium, Strobilanthes foliosus, Schkuhria pinnata, Sclerocarya birrea and Tabernaemontana elegans…..etc., recorded 10-100% efficiency against hard ticks within 24 hours to 14 days of treatment (Dantas et al, 2015;Ghosh et al, 2015a, b;Godara et al, 2015Godara et al, , 2018Banumathi et al, 2016;Cruz et al, 2016;Kumar et al, 2016;Muyobela et al, 2016;Singh et al, 2016;Anholeto et al, 2017;Rosado-Aguilar et al, 2017;Fouche et al, 2017Fouche et al, , 2019Vasconcelos et al, 2018;Figueiredo et al, 2019;Politi et al, 2019;Kemal et al, 2020;Upadhaya et al, 2020). Notably, the ticks killing activity of all extracts increases with increasing concentration and exposure time (Kemal et al, 2020).…”
Section: Discussionmentioning
confidence: 95%